Analisa Penggunaan Hasil Pembangunan Kapal Perang Modern di Galangan Indonesia untuk Mendukung Operasional TNI AL - Alfredo Panataran Purba; Firman Johan; Ugik Cahyo (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2024)
The current condition of modern warship construction in 2019 by Indonesia shipyard and Overseas shipyard, show several issues, including corrosion, problems with the air system and challenges related to electrical systems. Therefore, a root cause analysis is neede to identify the sources of theses problems. This study adopts a qualitative descriptive method that allows for a deeper and more flexible exploration of the technical issues ebcounted, utilizing data processing with Nvivo software. Additionally, a strategic analysis is conducted to elevate the strengths and weaknesses of the modern warship’sconstructions through a SWOT analysis approach. The types of data used in this research include primary data obtained through interviews and observations , as well as secondary data collected from relevant documents. The results indicate that 1) Corrosion on submarine is caused by coating applications and construction designs that are not in accordance with standards and lack of protection by cathodic protection systems. 2) Problems with the humidity are caused by sub-optimal design and insufficient diameter of the battery room ventilation branches. 3) In the electrical system, there were voltage spikes in the AC network and voltage distortions due to connected loads, such as inrush current and harmonics, as well as insulation problems in the DC-AC converter